Drawing as a Tool for Theatrical Costume Design: From Concept to Performance (Journal of the College of Basic Education, 2026)
This research aims to reveal the essential role of drawing in ambitious fashion design, as the first stage in transforming a dramatic idea into a tangible visual image that reflects the director and the artistic team. Initial drawings serve as a language of communication.Visually, it reduces lines, colors, and materials before transforming them into a realistic form on the stage. The research adopts the descriptive analytical method in studying the relationship between drawing and the theatrical idea, and analyzing the research sample in a descriptive way from the character of (Gilgamesh), which embodies the use of color and form as symbolic means expressing the dramatic conflict and heroism.The research concluded that theatrical sketching is not merely a design tool, but also an intellectual and aesthetic means of establishing the visual identity of costumes and linking the concept to the final product of the performance.